Local Wisdom of Wayang Figures: Building of Student Character (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This study aims to explore and analyze how character education can be developed through the integration of local wisdom, specifically using wayang (puppet) characters at Segulung 05 Elementary School. It investigates both the challenges and supporting factors in using wayang as a medium for character-building, and the overall impact on students. This approach is particularly interesting due to the deep cultural heritage of wayang on the island of Java, where each puppet character embodies moral values and life lessons that can be applied to everyday behavior. Methodology: This research utilizes a case study approach within a qualitative framework. Data was gathered through interviews, observations, and document analysis, focusing on the implementation of wayang in teaching moral values. Main Findings: The study reveals that character building through wayang involves not just storytelling but the use of wayang characters as moral role models, integrated into lessons in Javanese language and culture. Students engage with the rich symbolism of wayang, although variation in teaching methods is necessary to prevent disengagement. Despite potential challenges, wayang serves as an effective and captivating tool for instilling values, showing a positive impact on student character and increasing cultural awareness. Novelty/Originality of this Study: This study presents a novel approach to character education by incorporating traditional Javanese wayang as a teaching medium. It demonstrates that local cultural elements can serve as powerful tools for character development, contributing uniquely to educational practices and the preservation of cultural heritage.